2020
DOI: 10.1021/acssensors.0c01493
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Temperature-Dependent Interaction of Water Vapor with Tin Dioxide and Its Implications on Gas Sensing

Abstract: This work presents an operando infrared spectroscopic study of the temperature-dependent water adsorption on pristine SnO2 surfaces and discusses the possible implications on the oxygen ionosorption and gas-sensing mechanism. The impact of water on the sensor resistance, CO-sensing performance, and CO conversion was studied, and the obtained phenomenological results provide the basis for discussing the operando spectroscopic investigation findings. The provided information allows identification of three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…Fundamental investigations on the temperature interaction of water vapor over crystalline SnO 2 utilizing operando DRIFT spectroscopy confirmed, opposite to our dissociative adsorption mechanism, that neither physisorption nor dissociative water adsorption occurs over the surface of crystalline SnO 2 in the temperature range of 100–150 °C. On this account, theoretical vs experimental conditions should always be considered.…”
Section: Resultscontrasting
confidence: 85%
“…Fundamental investigations on the temperature interaction of water vapor over crystalline SnO 2 utilizing operando DRIFT spectroscopy confirmed, opposite to our dissociative adsorption mechanism, that neither physisorption nor dissociative water adsorption occurs over the surface of crystalline SnO 2 in the temperature range of 100–150 °C. On this account, theoretical vs experimental conditions should always be considered.…”
Section: Resultscontrasting
confidence: 85%
“…With the help of sensors, processes can be monitored, and thus limit values can be complied with. , In addition, the detection of gases such as CO and organic molecules plays an important role in the monitoring of exhaust gas emissions in the context of environmental protection. A widely used and well-studied sensing material with respect to ethanol gas sensing is tin oxide. Its sensor properties can be significantly improved by adding noble metals such as platinum or gold. , Regarding the influence of noble metal loadings on the sensor response, chemical and electronic influences have been discussed in the literature. In particular, two mechanisms, the spillover mechanism (chemical influence) and the Fermi-level control mechanism (electronic influence), have been used to explain the influence of noble metals on metal oxide gas sensors. , To the first approximation, one may assume either a dominant electronic or a dominant chemical influence of noble metals on the sensor response. , …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that in situ and operando Raman, ultraviolet–visible (UV–vis), and diffuse reflectance FT-IR spectroscopy (DRIFTS) are powerful (noninvasive) methods for mechanistic studies on metal oxide gas sensors. ,, By the combination of operando Raman/UV–vis spectroscopy and gas-phase FT-IR spectroscopy on tin oxide gas sensors, Elger and Hess were able to show that the sensing mechanism of tin dioxide during ethanol gas sensing is determined on the one hand by the formation and consumption of surface adsorbates and hydroxyl groups, and, on the other hand, by the formation of oxygen vacancies in the metal oxide. , In addition to ethoxy species, formate and acetate species were observed as surface adsorbates, and acetaldehyde, CO 2 , and water as gas-phase products of the oxidation of ethanol . These observations are in agreement with those obtained previously for indium oxide during ethanol gas sensing .…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, humidity also has to be considered, and it is very significant to investigate water adsorption to understand the surface chemistry of metal oxides. It has been discovered that H 2 O molecules have huge effects on the gas sensing properties of metal oxides, and certainly for α-MoO 3 . , Water adsorption at α-MoO 3 (100) has already been theoretically investigated, and it has found that E ads is about −1 eV for full coverage of H 2 O (each exposed Mo with one H 2 O molecule) . Herein, H 2 O adsorption at α-MoO 3 (100) in different coverages (1/8, 1/4, 1/2, and full) is simulated, as shown in Figure .…”
Section: Resultsmentioning
confidence: 98%